Pengaruh Penggunaan Media Digital Wordwall terhadap Peningkatan Keaktifan Belajar Pendidikan Agama Islam Peserta Didik Kelas VI di SD Negeri 010 Bontang Utara Tahun Pelajaran 2023/2024 - Khasanah, Lutfiana; Ihsan, Muh. (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This article discusses the influence of using digital media Wordwall towards increasing the activeness of classroom students' Islamic religious education learning VI at SD Negeri 010 North Bontang for the 2023/2024 academic year. Digital media Wordwall is a learning application that can simplify the learning process so this research aims to determine the impact of use learning applications and knowing the increase in learning activities students, the research method used is quantitative using a sample of 83 students. Data is collected through observation, interviews, questionnaires and documentation Apart from the impact, there has also been an increase active PAI learning through digital media Wordwall which produces results an increase of 13.9%. Based on the results of data processing and data analysis So it can be concluded that there is an impact from Wordwall digital media towards increasing active learning in Islamic religious education, along with its impacts Active learning about Islamic religious education through the media is also increasing digital word wall.